Pengaruh Pola Asuh dan Kebiasaan Belajar Terhadap Prestasi Belajar pada Materi Numerasi Siswa Sekolah Dasar - Ribka Inestya Simanungkalit; Susinah Kuntadi; Gatot Iwan Kurniawan (Program Studi Pendidikan Matematika, 2022)
The purpose of this study is to find out whether there is a relationship between parenting styles from parents and study habits on the learning outcomes of students in the Numeration material in class V SDN Banjaran VIII. This study uses correlational quantitative data collection techniques involving fifth grade students as respondents. The research instrument uses a questionnaire that has been tested for validity and reliability, involving 27 respondents, namely fifth grade students at SDN Banjaran VIII. Data analysis used correlational analysis, with F test and t test. The conclusions of this study are (1) simultaneously parenting from parents and study habits have an influence on student achievement, (2) parenting patterns from parents have an influence on student achievement, and (3) study habits have an influence on achievement student learning, especially on the Numerical material.